Analisis Media Pembelajaran Flash Card Untuk Anak Usia Dini - Ulfa, Noviana Mariatul (GENIUS: Indonesian Journal of Early Childhood Education, 2020)
Early Childhood Education is one of the educational institutions which is now a concern among the world of education. So that it has become a necessity for observers and education policy makers to pay attention and think of what strategies are best to be implemented in the implementation of learning in PAUD institutions. Learning strategies are defined as each activity, whether procedures, steps, methods or media chosen in order to provide convenience, facilities, and other assistance to students in achieving instructional goals. The learning strategies in early childhood always prioritize aspects of the activities of playing, singing (having fun), and working in the sense of activities. Playing, singing and doing activities are three characteristics of PAUD. Any aspect of education should be covered with active play, singing, and activities or work. These three things will hone brain intelligence, emotional intelligence, and physical skills that are carried out cheerfully, freely, and without burden. In the learning strategy contains various alternatives that must be considered to be chosen in the framework of teaching planning. To implement a certain strategy requires a set of teaching media. One of the learning media that can be chosen is flash card learning media.